O rapto de Europa: uma comparação entre Ovídio e Ticiano - Thamos, Márcio [UNESP] (My University, 2012)
In Metamorphoses, the Roman poet Ovid tells the tale of the transformation of Jupiter into a bull to seduce the Phoenician princess Europa. During Renaissance, as is well known, Western civilization fostered an intense renewal of its values under the clear influence of Greco-Roman culture. Ovid, whose fame had not ceased throughout the Middle Ages, became then even better known, and especially his poem Metamorphoses turned into a remarkable source of inspiration not only to literature but also to fine arts and their new humanistic conception. Thus, the episode of the abduction of Europa received a dramatic pictorial expression in the broad brush strokes of the Venetian master Titian Vecellio, who interpreted several classical myths in his canvases at the height of his creative maturity. There are many and obvious relationships in the verses of the ancient Latin poet and the picture of the Italian Renaissancist. In Metamorphoses, the mythical account is described in so many details and set in such an expressive poetic that Titian could take Ovid´s narrative as a model for painting “The Rape of Europa”, doing a true exercise in intersemiotic translation by interpreting verbal signs through pictorial signs.

Nas Metamorfoses, o poeta romano Ovídio narra a fábula da transformação de Júpiter em touro a fim de seduzir a princesa fenícia Europa. Durante o período do Renascimento, como se sabe, a civilização ocidental promoveu uma intensa renovação de seus valores sob a clara influência da cultura greco-romana. Ovídio, cuja fama não cessara por toda a Idade Média, tornou-se então ainda mais conhecido, e especialmente seu poema das Metamorfoses transformou-se em admirável fonte de inspiração não só para a literatura mas também para as artes plásticas e sua nova concepção humanista. Assim, o episódio do rapto de Europa ganhou uma dramática expressão pictórica nas largas pinceladas do mestre veneziano Ticiano Vecellio, que no ápice da maturidade criativa interpretou vários mitos clássicos em suas telas. Entre os versos do antigo poeta latino e o quadro do renascentista italiano há muitas e evidentes relações. Nas Metamorfoses, o relato mítico é descrito em tantos detalhes e fixado numa poética tão expressiva, que Ticiano pôde tomar a narrativa de Ovídio como modelo para pintar O rapto de Europa , fazendo então um verdadeiro exercício de tradução intersemiótica ao interpretar signos verbais através de signos pictóricos.PALAVRAS-CHAVE: O rapto de Europa ; Poesia; Pintura; Metamorfoses; Ovídio; Ticiano.THE RAPE OF EUROPA: A COMPARISON BETWEEN OVID AND TITIANABSTRACT: In Metamorphoses, the Roman poet Ovid tells the tale of the transformation of Jupiter into a bull to seduce the Phoenician princess Europa. During Renaissance, as is well known, Western civilization fostered an intense renewal of its values under the clear influence of Greco-Roman culture. Ovid, whose fame had not ceased throughout the Middle Ages, became then even better known, and especially his poem Metamorphoses turned into a remarkable source of inspiration not only to literature but also to fine arts and their new humanistic conception. Thus, the episode of the abduction of Europa received a dr
The rape of europa: a comparison between ovid and titian
Keywords: “The Rape of Europa”; Poetry; Painting; Metamorphoses; Ovid; Titian; “O rapto de Europa”; Poesia; Pintura; Metamorfoses; Ovídio; Ticiano